Local polynomial convexity of union of two graphs with CR isolated singularities - Kieu, Phuong Chi (H. : ĐHQGHN, 2017)
We give sufficient conditions so that the union of two graphs with CR isolated singularities in is locally polynomially convex at a singularly point. Using this result and some ideas in previous work, we obtain a new result about local approximation continuous function.